ANALISIS KEPEMIMPINAN, MOTIVASI, DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI DI KANTOR LURAH MEDAN PERJUANGAN - Tiara Okty Pratiwi Lubis; Muhammad Alfahmi (CV. ALIM'SPUBLISHING, 2024)
Employee performance can be seen from the quality and quantity achieved by an employee in carrying out his duties in accordance with the responsibilities given to him. This research aims to analyze leadership, motivation, and discipline and employee performance in the Medan Perjuangan Village Head. The sample in this study was 32 employees at the Medan Perjuangan Village Head. The data collection instrument uses a questionnaire with a Likert scale, each of which has been tested and has met the validity and reliability requirements. Data analysis used multiple linear regression using SPSS 19.0 for Windows software tools. The results of the partial research show that partial testing for the leadership variable shows a p-value of 0.303, meaning that partial leadership does not have a significant effect on employee performance in the Medan Perjuangan Village Head. The partial test results for the motivation variable show a p-value of 0.009, meaning that motivation partially has a positive and significant effect on employee performance at the Medan Perjuangan Village Head. The partial test results for the work discipline variable show a p-value of 0.000, meaning that discipline partially has a positive and significant effect on employee performance at the Medan Perjuangan Village Head. The results of the simultaneous testing of the calculated F value are 512.757 which is greater than 3.33 and the significant value of 0.000 is smaller than 0.05 so it can be concluded that leadership, motivation and discipline have a significant simultaneous effect on employee performance at the Medan Perjuangan Village Head.